Enhanced 3-Tier Storage Management Scheme For Flash Memory-Based Solid State Disk - Alsalibi, Ahmed I N (2017)
Nowadays, significant attention has been paid to the flash memory-based Solid State Disk (SSD). Different from traditional disks, SSD uses semiconductor chips for storing the data. This structure enjoys original technical characteristics including low power consumption, shock resistance and high performance in random access. Owing to these features, many devices are using flash memory as a basic storage component, such as mp3, smartphones, and tablet devices. However, the flash memory, basic unit of SSD, has many distinctive characteristics, which lead to multifarious challenges for example, writing data (storing data) is only allowed on empty storage unit (block), which makes it more time-consuming.